Fabrication and characterization of oxide-based resistive random access memory - Mohamed Hamzah Mohamed Abdul Kadir (2016)
Memory technologies have been gaining significant advancements in the infrastructure over the years. Factors that are seriously considered are high scalability, excellent and fast speed in operations, long retention ability, optimal endurance, energy-saving mode and the ease in integrating into a macro scale memory setup. With such factors into place, Resistive Random Access Memory (ReRAM) is one of such promising Non-Volatile Memory which tries to satisfy most of the factors as stated above. In this work, fabrication and characterization of oxide-based ReRAM would be the study. In specific, Magnesium Oxide (MgO) would be the main Oxide used, as it has been one of the most preferred compounds used for other similar study of MOS, MTJ and spin applications. Several factors for this choice are taken into consideration. Firstly a high breakdown field and a relatively good thermal conductivity, large band gap, and a good level of dielectric constant. It also has a low formation of interfacial layers, which is optimal for element disposition. Such attributes of MgO provide a good base to work with, in order to minimize, if not avoid, leakage currents during application of such a memory device. However there are also drawbacks to using MgO as oxide. They consume relatively high energy due to a high operating voltage. Such factors is taken into consideration in this work, with steps taken such as to deposit elements onto the devices to improve the device. The performance is then studied, with specific focus on its High and Low Resistance States. It is then discovered that much can be done to improve the performance of such devices, through more advanced techniques of characterization.